Factors Affecting Millennials' Decision to Choose a Mortgage and Trust as a Mediator - Patalo, Ryan Gerry (Jurnal Riset Inspirasi Manajemen dan Kewirausahaan, 2025)
This study aims to analyze and find out the factors that affect the decision of the millennial generation both partially and simultaneously in choosing mortgage products. The number of samples in this study was 215 respondents. The sampling technique uses random sampling. The data collection technique in this study uses a questionnaire. The analysis used in this study is multiple linear regression analysis. The results of the study show that the price level variable does not have a significant effect on the customer's decision to choose a mortgage product, but after there is a confidence variable, it becomes influential. Then the variables of service quality and procedures do not have a significant effect on the customer's decision to choose a mortgage product after the trust variable as a mediator.